2008
DOI: 10.1093/gerona/63.11.1227
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ACTN3 Genotype and Physical Functioning With Age in Older Adults

Abstract: Objective The purpose of this study was to examine the association of the alpha-actinin-3 (ACTN3) R577X polymorphism on muscle function and physical performance in older adults. Methods We measured knee extensor torque, midthigh muscle cross-sectional area, muscle quality, short physical performance battery score, and 400-meter walk time at baseline and after 5 years in white older adults aged 70–79 years in the Health, Aging and Body Composition Study cohort (n = 1367). Incident persistent lower extremity l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…The present study of a large Japanese cohort confirmed that subjects with the ACTN3 RR or RX genotype possess greater lower-extremity muscle function, which is in agreement with the results of previous studies in the Caucasian population (Walsh et al 2008) and athletes (Yang et al 2003;Kikuchi et al 2013). Delmonico et al (2008) demonstrated that the ACTN3 R577X genotype was associated with a change in the performance phenotype after at least 4 years of aging in a large cohort of elderly subjects. This study suggested that the ACTN3 XX genotype may play a small role in the age-associated decline in 400-m walking time in male subjects and may increase the risk of functional limitation in female subjects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study of a large Japanese cohort confirmed that subjects with the ACTN3 RR or RX genotype possess greater lower-extremity muscle function, which is in agreement with the results of previous studies in the Caucasian population (Walsh et al 2008) and athletes (Yang et al 2003;Kikuchi et al 2013). Delmonico et al (2008) demonstrated that the ACTN3 R577X genotype was associated with a change in the performance phenotype after at least 4 years of aging in a large cohort of elderly subjects. This study suggested that the ACTN3 XX genotype may play a small role in the age-associated decline in 400-m walking time in male subjects and may increase the risk of functional limitation in female subjects.…”
Section: Discussionsupporting
confidence: 92%
“…However, a meta-analysis by Alfred et al (2011) showed that while the ACTN3 R577X genotype is associated with sprint and power athletic status in Europeans, this genotype does not appear to be associated with muscle phenotypes in the general population. Delmonico et al (2008), in their longitudinal study, reported that the ACTN3 R577X genotype may be associated with a decline in certain measures of physical performance with age, particularly in older populations. However, they also concluded that the ACTN3 R577X genotype does not appear to have a strong effect on muscle phenotypes, based on the strength and consistency of the associations and the lack of replication of specific phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further addressing this field of inquiry, the final two articles of the Journal also use prospective study designs to assess the potential role of variation in two particular genes and risk for healthy aging and longevity. The first article, that of Delmonico and colleagues (59), examined the association of variation within the alpha-actinin-3 (ACTN3) gene on muscle function and physical performance in older adults. The ACTN3 R577X polymorphism predicted decline in some performance variables with age in men and women.…”
Section: Global Approaches To Understanding Healthy Aging: the Role Omentioning
confidence: 99%
“…myostatin gene ( MSTN ), angiotensin converting enzyme gene ( ACE ), peroxisome proliferator-activated receptor-γ coactivator 1α ( PGC-1 α), hypoxia-inducible factor-1 ( HIF-1 ) and others (Buchner et al, 1993; Spurway and Wackerhage, 2006). Therefore, only a small number of genes containing single nucleotide polymorphisms (SNPs) have been identified as candidate genes for explaining this variability (Delmonico et al, 2008). One of them is alpha-actinin-3 gene ( ACTN3 ), which encodes the protein a-actinin-3.…”
Section: Introductionmentioning
confidence: 99%